Analisis Permintaan Alat Kapal pada PT. Prima Multi Peralatan - Zikri Rahman; Muhammad Yafiz (Jurnal Multidisiplin Dehasen (MUDE), 2022)
This paper is motivated by research at the internship at PT. Prima Multi Equipment. This study aims to analyze the demand for goods and what are the factors that influence the PT. Prima Multi Equipment in the period July 2021 – January 2022. The observed data were taken directly from the staff at PT. Prima Multi Equipment and through interviews and get results in the form of demand for goods is strongly influenced by the factors that influence it. This paper is motivated by research at the internship at PT. Prima Multi Equipment. This study aims to analyze the demand for goods and what are the factors that influence the PT. Prima Multi Equipment in the period July 2021 – January 2022. The observed data were taken directly from the staff at PT. Prima Multi Equipment and through interviews and get results in the form of demand for goods is strongly influenced by the factors that influence it.